A Cointegration and Causal Analysis of the Government Revenue and Expenditure Relationship in Indonesia - Rijoly, Jacobus Cliff Diky; Sapulette, Shella Gilby; Latuamury, Jabida; Usmany, Alfrin Ernest Marthin; Limba, Franco Benony (Journal of Business & Banking, 2022)
This study aims to discuss the causal analysis of government revenues and expenditures in Indonesia in light of the fact that Indonesian fiscal policy significantly relies on government finance. Therefore, it can lead to fragile macroeconomic conditions. In addition, to illustrate this occurrence, the researchers used Granger causality method on data from 1971 to 2021 provided by the World Bank. This paper's findings indicate that in Indonesia, the long run or equilibrium relationship between government revenue and government expenditure goes from government expenditure to government revenue. In addition, this conclusion demonstrates that government expenditures affect government revenue.